Don't worry, dear - Fassler, Joan.; Kranz, Stewart (New York Behavioral Publications, 1971)
Jenny's mother patiently waits for her to outgrow her thumb-sucking, bedwetting, and stuttering.
Keywords: Behavior -- Fiction